42 SEASON VARIABILITY IN ATHEROSCLEROSIS COMPOSITION: INSIGHTS FROM 1848 NON-CULPRIT CORONARY PLQUES. (15th December 2022) - Sammartini, Emanuele; Biccirè, Flavio Giuseppe; Debelak, Caterina; La Porta, Ylenia; Budassi, Simone; Varricchione, Giuseppe; Romagnoli, Enrico; Marco, Valeria; Boi, Alberto; Fineschi, Massimo; Fabbiocchi, Franco; Taglieri, Nevio; et al.
Abstract: Background: Several environmental and seasonal factors are thought to be crucial in the risk of acute coronary syndromes (ACS), including temperature, latitude, longitude, atmospheric air pressure, wind velocity and circadian period. However differences in coronary plaque composition according to season variation is still poorly understood. Purpose: Our study aims to analyse the characteristics of non-culprit coronary plaques in patients undergoing optical coherence tomography evaluation (OCT) evaluation of the left anterior descending artery. Methods: We included 1848 non-culprit coronary plaques from 1003 patients of the CLIMA registry. The season of OCT pullback acquisition was collected for each patient. Results: Overall, median age was 66 years (56-74), with 24.6% of women and 53.4% of ACS. At patient-level analysis, patients admitted in summer were less frequently affected by hypertension (59.8% vs 69.4% in autumn, 68.5% in winter and 72% in spring; p=0.027) and chronic kidney disease (14.8% vs 15.9% in autumn, 10.3% in winter and 19.4% in spring; p=0.037) in. At lesion-level analysis, similar values of fibrous cap thickness, maximum lipid arc, length of plaques and presence of macrophages were observed (Table 1 ). Summer plaques had a smaller minimum lumen area than spring plaques (5.7±3.1 vs 5.1±239; p=0.044) and also a less frequent superficial macrophage infiltration (23% vs 36.1% in autumn, 30.5% in winter and 30.6% in spring; p=0.030) and presence of cholesterol crystals (16.7% vs 23.8% in autumn, 28.4% in winter and 22.1% in spring; p=0.037 than three other season). Table 1 Conclusions: Coronary plaques during summer had less local sign of inflammation such superficial macrophage infiltration and cholesterol crystals. Further studies are needed to confirm these results and investigate clinical implications.